Simulasi dan Analisis Sistem Pengatur Tegangan DC Menggunakan Rangkaian Push-Pull Converter - Feri Yusivar; Lintang Hapsari Wilujeng (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
A problem that often encountered in sources voltage especially DC (Direct Current) voltage sources are far below the working voltage levels that are generally used in residential electrical grid system. To handling the problems of the DC voltage source, one way that can be taken is to implement a DC voltage converter circuit or DC-DC Converter. In this paper, a series of isolated type DC-DC Converters, namely Push-Pull Converter, is being promoted. The Selection of Push-Pull Converter based on reliability and quality of generated power among others, ease of applicability and the most important is the robustness of the interference that may occur. The system is controlled by a simple linear controller, such as Proportional Integral (PI) controller or Integral Proportional (IP) controller. System’s stability is also tested using Bode plots. From simulation results and stability analysis, it can be conclude that the Push-Pull converter circuit resists against disturbance.